2020
DOI: 10.3390/foods9020223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roasting Time and Cryogenic Milling on the Physicochemical Characteristics of Dried Ginseng Powder

Abstract: This study aimed to evaluate the effect of reduced particle size of ginseng by roasting and cryogenic milling on increasing its water solubility and physiological activity. The samples were roasted for different times (9–21 min) and generated in different sizes (10–50, and >50 μm). All roasted samples revealed significantly smaller particle sizes than did non-roasted samples, based on Sauter mean diameter (D [3,2], p < 0.05). Furthermore, the particle sizes of roasted samples decreased until roasting up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The inverse relation of PSD and span factor was reported by Kong et al [38] and Khaleel et al [37]. The current data can be supported with the findings of Jeong et al [60] for the roasted ginseng powder. They reported that ginseng roasted at 180 °C up to 15 min showed a decreasing pattern for particle size due to destruction in starch granules and starch-protein interactions, but prolonged exposure for over 18 min caused a significant increase in particle size due to flocculation.…”
Section: Particle Size Distribution (Psd)supporting
confidence: 91%
“…The inverse relation of PSD and span factor was reported by Kong et al [38] and Khaleel et al [37]. The current data can be supported with the findings of Jeong et al [60] for the roasted ginseng powder. They reported that ginseng roasted at 180 °C up to 15 min showed a decreasing pattern for particle size due to destruction in starch granules and starch-protein interactions, but prolonged exposure for over 18 min caused a significant increase in particle size due to flocculation.…”
Section: Particle Size Distribution (Psd)supporting
confidence: 91%
“…Our results are similar to those reported before. For example, Jeong et al [32] found that the content of TPC increased significantly after baking dry ginseng powder, probably because Maillard reaction products with a phenol structure were produced during baking, which increased the content of TPC. Jin et al [33] found that the content of TPC increased significantly after baking ginseng roots at 140-200 • C and speculated that baking would transform the combined polyphenol compounds into free polyphenols to increase the content of TPC.…”
Section: The Effect Of Fir Heat Treatment On the Tpc In American Gins...mentioning
confidence: 99%
“…The 2,2-diphenyl-1-picrylhydrazyl (DPPH; Sigma-Aldrich, St. Louis, MO, USA) content of cooked meat analog was measured using a modified Jeong method [26] to determine the free-radical-scavenging activity in the cooked meat analog. One gram of freeze-dried meat analog was extracted with 25 mL of 70% ethanol for 3 h in a water tank (BF-30SB; Biofree, Seoul, Republic of Korea) set at 80 • C. The extract was filtered through Whatman No.…”
Section: Dpph-radical-scavenging Activitymentioning
confidence: 99%